AUTOMATA SEBAGAI MODEL PENGENAL BAHASA - Eddy Maryanto (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2009)
A deterministic finite automaton as well a nondeterministic finite automaton can be used to model a language recognizer. In computer software technology, language recognizer usually be an integrated part of a compiler, that is a computer program that take responsibility to translate source code into machine code. Comparing with a deterministic finite automaton, a nondeterministic finite automaton is a better model for language recognizer because it might be simpler and less in size than a deterministic one.